2016
DOI: 10.2174/1570161114666160222115158
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide is a Central Common Metabolite in Vascular Dysfunction Associated with Diseases of Human Pregnancy

Abstract: Preeclampsia (PE), gestational diabetes mellitus (GDM), and maternal supraphysiological hypercholesterolaemia (MSPH) are pregnancy-related conditions that cause metabolic disruptions leading to alterations of the mother, fetus and neonate health. These syndromes result in fetoplacental vascular dysfunction, where nitric oxide (NO) plays a crucial role. PE characterizes by abnormal increase in the placental blood pressure and a negative correlation between NO level and fetal weight, suggesting that increased NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 289 publications
1
27
0
Order By: Relevance
“…In addition, pregnant women have a three times greater risk of dying from flu and malaria than nonpregnant (NP) women [2], suggesting that pregnant women are particularly vulnerable to some types of infection. This may be related to various pregnancy-induced adaptations: (i) suppression of the acquired immune system [3]; (ii) excessive activation of the innate immune system, which is thought to be responsible for preterm labor (PTL) [4] and some cases of cerebral palsy [5]; and (iii) higher levels of nitric oxide may exacerbate sepsis-induced hypotension and enhance the excessive innate immune response [6,7]. Although septic shock is a major cause of mortality in intensive care units worldwide, remarkably little is known about the impact of sepsis on cardiovascular function during pregnancy [8], especially the adaptation and regulation of the peripheral vascular system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pregnant women have a three times greater risk of dying from flu and malaria than nonpregnant (NP) women [2], suggesting that pregnant women are particularly vulnerable to some types of infection. This may be related to various pregnancy-induced adaptations: (i) suppression of the acquired immune system [3]; (ii) excessive activation of the innate immune system, which is thought to be responsible for preterm labor (PTL) [4] and some cases of cerebral palsy [5]; and (iii) higher levels of nitric oxide may exacerbate sepsis-induced hypotension and enhance the excessive innate immune response [6,7]. Although septic shock is a major cause of mortality in intensive care units worldwide, remarkably little is known about the impact of sepsis on cardiovascular function during pregnancy [8], especially the adaptation and regulation of the peripheral vascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies reported that moderate iron intake in non‐anemic pregnant women could induce glycemic disorder, hyperinsulinemia and oxidative damage in their offspring, and that fetal hyperinsulinemia was positively correlated with macrosomia. Interestingly, both pregnant women and their newborns showed euglycemia after treatment with diet; however, metabolic alternation of OS in the fetoplacental vasculature was seen, including endothelial dysfunction, which was likely associated with hyperinsulinemia of the fetus and thereby leading to macrosomia. Although their PG was normal, non‐GDM pregnant women with a high concentration of plasma ferritin might induce fetal hyperinsulinemia and oxidative damage in their offspring, leading to metabolic alternation by OS; thereby, it was likely associated with macrosomia.…”
Section: Discussionmentioning
confidence: 95%
“…16 These findings add to previously reported work suggesting a link between maternal and fetal nitrogen oxide metabolism and disease. 17, 18 …”
Section: Discussionmentioning
confidence: 99%